Development of a Magnetic Attachment Method for Bionic Eye Applications. Issue 3 (29th September 2015) - Fox, Kate; Meffin, Hamish; Burns, Owen; Abbott, Carla J.; Allen, Penelope J.; Opie, Nicholas L.; McGowan, Ceara; Yeoh, Jonathan; Ahnood, Arman; Luu, Chi D.; Cicione, Rosemary; Saunders, Alexia L.; et al.
Abstract: Successful visual prostheses require stable, long‐term attachment. Epiretinal prostheses, in particular, require attachment methods to fix the prosthesis onto the retina. The most common method is fixation with a retinal tack; however, tacks cause retinal trauma, and surgical proficiency is important to ensure optimal placement of the prosthesis near the macula. Accordingly, alternate attachment methods are required. In this study, we detail a novel method of magnetic attachment for an epiretinal prosthesis using two prostheses components positioned on opposing sides of the retina. The magnetic attachment technique was piloted in a feline animal model (chronic, nonrecovery implantation). We also detail a new method to reliably control the magnet coupling force using heat. It was found that the force exerted upon the tissue that separates the two components could be minimized as the measured force is proportionately smaller at the working distance. We thus detail, for the first time, a surgical method using customized magnets to position and affix an epiretinal prosthesis on the retina. The position of the epiretinal prosthesis is reliable, and its location on the retina is accurately controlled by the placement of a secondary magnet in the suprachoroidal location. The electrode position above the retina is less than 50 microns at the center of the device, although there were pressure points seen at the two edges due to curvature misalignment. The degree of retinal compression found in this study was unacceptably high; nevertheless, the normal structure of the retina remained intact under the electrodes.